A Case for Deductive Teachers’ Perception using Inductive Instruction in Teaching English Grammar for Junior Students - Rismayanti, Luh Ayu (Journal of Education Research and Evaluation, 2021)
In order to know the effectiveness of method used in teaching grammar, a study about perception is quite recommended to be explored. Several studies about grammar have been conducted by other researcher but a lack of research conducted to indicate teacher perception toward the method in teaching grammar. Thus, this qualitative research design with case-study was conducted. This study investigated the perception of teacher especially who use deductive more routine toward the use of inductive approach in teaching grammar. The research instruments used are observation, document analysis, and interview guide. The collecting data were obtained through observation sheet, lesson plans analysis, and interview. Although, it was found that English teachers in SMPN 3 Sawan generally prefer deductive approach, it doesn’t mean they were not using inductive approach at all. The finding indicates positive perception from deductive teachers toward inductive instruction in teaching grammar concluded from interview session.